Microsoft Office 2013 : ProjectLearn - Coulthard, Glen J. (McGraw-Hill Education, 2014)
This book is a new series by McGraw-Hill with a project-based approach for engaging students in learning Microsoft Office 2013. This approach guides students to the end result, and the projects they complete become a quality portfolio of their work they can then carry with them throughout their careers. This highly structured series offers students two projects per chapter with a varying number of lessons within each project. Each lesson provides a consistent farmwork for learning office 2013 skills, including lesson overview, skills preview, and project practice sections....